The Influence of Gaze-Augmented Reflection on Students' Problem Solving - Langner, Axel Dinesch; Justus Liebig University Giessen (My University, 2026)
Problem-solving activities support conceptual understanding and the development of competencies needed to resolve problems and make informed decisions. In organic chemistry, problem solving relies heavily on representations that encode both explicit and implicit information. However, students often struggle to use These representations in their problem solving.
Although various instructions have been shown to support problem solving with representations, they often benefit only specific subgroups of students. In contrast, reflection on one’s own problem solving—enhanced by showing students their eye movements and providing guiding prompts in an eye-gaze-augmented retrospective—offers a differentiated and personalized approach. This Dissertation investigated the influence of such gaze-augmented reflection on students’ Problem solving in two exploratory studies—with and without the retrospective.
This investigation integrates and extends the methodological and empirical foundations established in:
Langner A. & Graulich N. (2024). From sight to insight – reflection processes in an eye-gaze-augmented retrospective. International Journal of Science Education, 1–24. https://doi.org/10.1080/09500693.2024.2430804
Langner A., Hain L., & Graulich N. (2025). Defining Areas of Interest in Organic Chemistry Education Eye-Tracking Research. Journal of Chemical Education, 102(3), 1285–1297. https://doi.org/10.1021/acs.jchemed.4c00830
Langner A., Sahba M., Popova M., & Graulich N. (2025). An Integrated Approach to Characterizing Changes in Organic. Journal of Chemical Education. https://doi.org/10.1021/acs.jchemed.5c00849
The findings indicate that gaze-augmented reflection was associated with more goal-driven allocation of attention and that, despite highly individual trajectories shaped by initial problem-solving accuracy and student characteristics, accuracy converged across students. Overall, these findings highlight the potential of gaze-augmented reflection as a personalized approach to supporting students’ problem solving with representations.
Keywords: Chemistry Education Research; Chemistry Education; Eye-Tracking; Eye Movements; Reflection; Problem Solving; ddc:540; ddc:370